PENERAPAN METODE PIECES DALAM EVALUASI APLIKASI PEDULI LINDUNGI - Kevin Septianzah; Irawan Setiadi; Imam Himawan (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
Abstract Starting with the COVID-19 pandemic which caused instability in all sectors, especially in the industrial sector, all were affected, for example for companies that were developing or already advanced, disrupting the FIFO (First In First Out) cycle which resulted in risks that led to losses, which has reached the BEP number. (Break Event Point) alone is enough, but for the current situation, it is very difficult to develop so far to survive, that is enough, therefore the government issued a policy towards the people in Indonesia, regarding a free-based application called Peduli Protect to protect the community. can assist the government in the tracking process. Through Peduli Protect, the government will make it easier to detect the flow of the spread of COVID-19. In addition, it can also be seen that every close contact that occurs between individuals as an effort to limit the growth of covid19. At first the Peduli Protect application was still very limited in number of users, with the passage of time, the Peduli Protect application continued to improve its functions. One of its functions is access to vaccine certificates, screening visiting, tracking records of domestic and international traveling. The Peduli Protect application can be used on two operating systems such as Android and iOS. In this research, a problem is raised regarding the complexity of information that often occurs, such as an example of updating information, therefore the author raises the topic of discussion regarding the application of the pieces method to the Peduli Protect application, to ensure that the application when compared to this method can be measured as much as possible against information data. which is obtained in a complex manner . Keywords: Covid19; Peduli Lindungi; PIECES; Evaluation Spesification; Prototype